Integumental lips’ height and separation in different Angle’s classes of malocclusions - Afrah Kh Al–Hamdany (Al-Rafidain Dental Journal, 2007)
Aims: To reveal the possible soft tissue difference in the upper and lower lip heights, separations and coverage of lower lip to upper incisors in different Angle’s classes of malocclusion, to determine any difference in the mean between males and females for each variable and to find any correlation among the variables. Materials and Methods: Nightly nigh students (52 males, 47 females), 20–23 years of age that was randomly selected from the college of dentistry, University of Mosul.The overall sample was classified depending on Angle’s classification of malocclusion into four groups (Class I, II.1, II.2 and III). For each group, four facial soft tissue variables were measured directly using electronic digital viernier caliper. Results: A major findings that emerged from the research is that the Class I subjects possessed higher values of upper lip length followed by Class II then Class III, this difference is significant between Class I,III and II,III and non significant between I,II. Where as Class III subjects possessed non significant higher values of lower lip length followed by Class II then Class I. The lip separation value is non significantly higher in Class II subjects followed by Class III then Class I. While Class III subjects possessed non significant higher values of lower lip to incisor superior followed Class I then Class II. Conclusions: For each specific Angle’s class of malocclusion, a specific facial soft tissue parameters. The upper lip length is greater in Class I subjects. Class III subjects have the greater lower lip length. The inter–labial gap is larger in Class II subjects.While the coverage of the lower lip to incisor superior is greater in Class III subjects. Most of the variables are higher in males than females. Complex correlations among the studied variables are found that varied between weak to high positive or negative with varying degree of significance.